Contribuições para o estudo do compensador síncrono baseado em máquina de indução duplamente alimentada - Silva, Paulo Henrique Pereira (2018)
The supply of energy plays a key role in today’s world for the development of nations. Adequate provision of this energy is increasingly important, given the complexity and sensitivity of the equipment used to operate it properly. On the other hand, arrangements with induction machines, such as the Doubly Fed Induction Generator (DFIG), have potential for use in reactive compensation, which goes beyond its most common application in eolioelectric generation, helping to improve energy quality. In this context, this paper presents contributions to the study of the use of DFIG as a synchronous compensator. Four different control strategies are analyzed in order to provide power compensation for the cases of networks with voltage unbalance. The mathematical modeling was developed based on the sequence separation method and later validated through simulations carried out by PSCAD / EMTDC software and experimental tests in the laboratory. The results showed that the developed control reduced the oscillating sine and cosine components present in the active and reactive powers, as well as mitigated the oscillations in the rotor and stator currents of the machine, coming from negative sequence. In this way, the proposed compensator was able to process power in a bus that was in voltage unbalance. This paper contains arguments that point out that the proposed model has the potential to be used in favor of improving the quality of electric energy.